The concept of right and duty in philosophy - Karrar Buraq Talib, Assist. Lect. (Basra studies journal, 2025)
This research explores the philosophical concepts of rights and duties, examining their types and their significance in regulating social relations and achieving a balance between individual freedom and social responsibility. The study demonstrates that a clear understanding of rights contributes to the promotion of justice and freedom, while duties reinforce both individual and collective responsibility—fostering the development of more stable and equitable societies. The research emphasizes the importance of enhancing philosophical and ethical awareness of these two concepts and advocates for the development of policies that promote balanced and responsible social interactions. It also highlights the need to support future research that deepens our understanding of the social and ethical dimensions of rights and duties in contemporary societies.